2017
DOI: 10.1109/lra.2017.2678546
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Joint and Hand Impedance During Teleoperation and Free-Hand Task Execution

Abstract: Teleoperated robotic surgery allows filtering and scaling the hand motion to achieve high precision during the surgical interventions. Teleoperation represents a very complex sensory-motor task, mainly due to the kinematic and kinetic redundancies that characterize the human motor control. It requires an intensive training phase to acquire sufficient familiarity with the master-slave architecture.We estimated the hand stiffness modulation during the execution of a simulated suturing task in teleoperation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Importantly, the specific parameters of the power law will have to be determined as part of the controller design, or alternatively, may be left as a tuning parameter for the user. This framework can also be relevant to other applications of teleoperation [73][74][75], shared control [76,77], devices such as exoskeletons [78] and prostheses, and even trajectory generation for autonomous systems [79,80].…”
Section: Teleoperationmentioning
confidence: 99%
“…Importantly, the specific parameters of the power law will have to be determined as part of the controller design, or alternatively, may be left as a tuning parameter for the user. This framework can also be relevant to other applications of teleoperation [73][74][75], shared control [76,77], devices such as exoskeletons [78] and prostheses, and even trajectory generation for autonomous systems [79,80].…”
Section: Teleoperationmentioning
confidence: 99%
“…Instead of freezing the arm joints in the same solutions, experts exploit this redundancy, and use this variability in their arm joints to increase performance. To develop intuitive teleoperation systems and controllers, and to further understand redundancy exploitation in the human arm, it is beneficial to model the exploitation of arm kinematic and kinetic redundancy in different teleoperation and manipulation conditions [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Burdet et al, 2001 ) demonstrated the existence of control strategies employed to achieve stability through the regulation of the arm endpoint stiffness in terms of maximal value and orientation. Other studies showed the importance of stiffness regulation during complex tasks execution and motor learning (Osu et al, 2002 ; Gribble et al, 2003 ; Buzzi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 95%